Development of counting skills screening and training support system for special children ages 5 to 8 years old - 277753 Dyg. Azmawati Abg. Abdul Samad; Eko Suprianto, supervisor; Fakulti Kejuruteraan Elektrik (2008)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2008